Performance of the GRACE scores in a New Zealand acute coronary syndrome cohort. Issue 24 (4th September 2014) - Lin, Aaron; Devlin, Gerry; Lee, Mildred; Kerr, Andrew J
Abstract : Background: Risk stratification after acute coronary syndrome (ACS) event is recommended to guide intensity and timing of investigation and management. The Global Registry of Acute Coronary Events (GRACE) investigators have published several scores for predicting patient risk both at hospital admission and discharge. Objective: To evaluate the performance of the admission-to-6-month and discharge-to-6-month GRACE scores for predicting myocardial infarction (MI) and mortality in a contemporary cohort of patients admitted with ACS. Methods: The cohort comprised 3743 consecutive patients admitted to cardiology services in two large New Zealand hospitals with an ACS between 2007 and 2011. Risk score data was collected in an electronic registry and linked anonymously to national hospitalisation and mortality records. Results: Between admission and 6 months, 160 patients died and another 269 were rehospitalised with an MI. The GRACE admission-to-6-month total mortality and mortality/MI scores both overestimated event rates approximately twofold. The discharge-to-6-month mortality equation was better calibrated. Global discrimination was very good for both admission-to-6-month and discharge-to-6-month mortality scores (c=0.805 and c=0.795, respectively) and moderately good for the corresponding mortality/MI equations (c=0.652 and c=0.624, respectively). Conclusions: In a contemporary ACS cohort, the GRACE discharge-to-6-month mortality score has very good discrimination and accurately predicts mortality rates, whereas the admission-to-6-month equation, despite good discrimination, overestimated risk. Recalibration or more dynamic modelling of inhospital risk which includes variables such as time from admission to risk assessment are needed to support use of ACS risk assessment inhospital.